Science and innovation policies in North African Countries: Exploring challenges and opportunities - (:unkn) unknown (My University, 2018)
Effective science, technology and innovation (STI) policies and strategies reflect a country's successful contribution to scientific advancement. While the economic and geopolitical framework of many North African Countries (NACs) transformed enormously during the past decades, their relevant policies and performance were not responsive enough in adapting to these dynamics. This review is meant to highlight the current development and evolution of NAC's STI policies as well as similarities and identified common societal challenges within NACs. It focusses on the nexus approach to water, energy and food. The findings of this review suggest that the existing reform and development of the STI system in NACs require reorientation towards higher socioeconomic relevance and innovation focus accompanied by legislative measures, effective monitoring and evaluation tools as well as engagement of relevant stakeholders and the adequate leverage of sufficient strategic investments.
Keywords: African Research